FORMULASI DAN UJI AKTIVITAS ANTIBAKTERI SALEP EKSTRAK ETIL ASETAT BATANG KECOMBRANG (Etlingera elatior (Jack) R.M.Sm.) TERHADAP BAKTERI Pseudomonas aeruginosa - Linda Nur Azizah; Galih Samodra (Pharma Xplore : Jurnal Sains dan Ilmu Farmasi, 2022)
Kecombrang stems contain flavonoid compounds, alkaloids, saponins and tannins that have the potential to inhibit bacterial growth. This study aims to determine the physical properties, stability and antibacterial activity of the ethyl acetate extract of kecombrang stem ointment.This type of research is an experimental laboratory. Extraction using maceration method with ethyl acetate solvent. The concentrations of the extracts used were F1 (10%), F2 (15%) and F3 (20%). Testing of physical properties seen from organoleptic, homogeneity, pH, adhesion and spreadability. The results were analyzed by One Way Anova and there were significant differences in the pH value, adhesion and dispersion. Formulas 1, 2 and 3 can inhibit Pseudomonas aeruginosa bacteria with an average inhibition zone of (F1) 8.02 mm, (F2) 9.34 mm and (F3) 11.00 mm. Based on this research, it can be concluded that F3 is the best formula with a strong inhibition zone, while F1 and F2 have moderate inhibition.